The rise and rise of financial technology: The good, the bad, and the verdict - Nofie Iman (Taylor & Francis Group, 2020)
While the use of the term fintech or financial technology has proliferated widely, theoretical work on the concept has lagged behind. This article attempts to capture the discussion on fintech, to provide a critique of the literature, and to propose future research opportunities. In order to do so, a list of peer-reviewed journals was compiled, identified, examined, coded, and classified into high-level themes to be reviewed, analysed, and interpreted. After synthesising the notion of fintech in the literature, this article proposes several potential areas for further exploration, divided into the following themes: definition, attributes, adoption, regulation, and competition. Fintech or financial technology is a relatively new subject in the literature but commonly cited as one of the most important innovations in the financial industry. It is expected that this article will help researchers and academics who are interested in studying the phenomenon more broadly.